Knowledge Attitude And Practice Regarding Superficial Fungal Infections In Dermatology Patients In Eastern Nepal - Yamu, Sabrina; Choudhary, Dilip; Aryal, Shweta (Birat Journal of Health Sciences, 2024)
Introduction: Superficial fungal infection is one of the most common diseases in dermatology evolving like an epidemic. Hence further research is necessary to minimize the occurrence and prevention of the disease. Objectives: To assess the knowledge, attitude and practice about superficial fungal infection and implicate the result in educating the patients thereby minimizing its further recurrence and re-infections. Methodology: A hospital based observational descriptive quantitative crosssectional study was conducted in all patients with superficial fungal infections attending dermatology outpatient department at Birat Medical College Teaching Hospital. A selfdesigned questionnaire which was double translated by two individuals in different translations and validated was used to assess knowledge, attitude and practice (KAP) regarding superficial fungal infections. Data were entered in Microsoft excel and analyzed in terms of proportions and percentage. Results: Out of total 162 patients participating in the study, less than half of the study population was aware that it was a fungal infection; majority did not know how to apply medication in an appropriate technique. They strongly believed that hot weather was the cause. They practiced daily bath, but did not change their clothes often. They preferred taking over the counter medications and visited dermatologists less often and did not complete the total dose of prescribed medication and shared their prescription with their family members for similar problem. Consclusion: All clinicians treating with superficial fungal infection should emphasize on counseling the patients regarding behavioural changes which will not only aid in treatment but will also focus on its preventive aspect.